2021
DOI: 10.1002/open.202100204
|View full text |Cite
|
Sign up to set email alerts
|

A Naphthalimide‐Based Fluorescent Probe for the Detection and Imaging of Mercury Ions in Living Cells

Abstract: The selective and efficient monitoring of mercury (Hg 2 + ) contamination found in the environment and ecosystem has been carried out. Thus, a new 1,8-naphthalimide-based fluorescent probe NADP for the detection of Hg 2 + based on a fluorescence enhancement strategy has been designed and synthesized. The NADP probe can detect Hg 2 + with high selectivity and sensitivity and a low detection limit of 13 nm.The detection mechanism was based on a Hg 2 + -triggered deprotection reaction, resulting in a dramatic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Amongst the various aldehyde protective groups, multistep synthesis in cyclic or acyclic thioacetals is frequently engaged, as they are stable in all conditions containing acidic and alkaline media. Furthermore, signaling mechanisms that commonly arise in fluorescent probes are intramolecular charge transfer (ICT), [12][13][14][15][16][17] photo-induced electron transfer (PET), 18 fluorescence resonance energy transfer (FRET), 19 which are ascribed in the direction of energy/electron transfer using protection/ deprotection approach. Many fluorometric sensor moieties are available for the detection of mercury but with limitations, for example, pyridine and pyrene molecules are very difficult to synthesize and are less sensitive and less specific.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the various aldehyde protective groups, multistep synthesis in cyclic or acyclic thioacetals is frequently engaged, as they are stable in all conditions containing acidic and alkaline media. Furthermore, signaling mechanisms that commonly arise in fluorescent probes are intramolecular charge transfer (ICT), [12][13][14][15][16][17] photo-induced electron transfer (PET), 18 fluorescence resonance energy transfer (FRET), 19 which are ascribed in the direction of energy/electron transfer using protection/ deprotection approach. Many fluorometric sensor moieties are available for the detection of mercury but with limitations, for example, pyridine and pyrene molecules are very difficult to synthesize and are less sensitive and less specific.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various uorescence assays have been developed to detect Hg 2+ due to their unique advantages, such as rapid analysis and high sensitivity and selectivity. [9][10][11][12][13][14] In particular, Hg 2+ uorescence detection based on various uorescent nanomaterials has been widely reported; for example, sensors based on Hg 2+ induced uorescence quenching were developed for the determination of Hg 2+ using semiconductor quantum dots (QDs), 15 metal nanoclusters, 14,16 and carbon nanomaterials. 17 Wang et al 15 reported a label-free sensor for Hg 2+ detection in tap water, river water, and wastewater treatment plant effluent based on CdSe/ZnS quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics classify them as ideal chromophores for developing probes, particularly for detecting mercury. Several studies in literature have already reported the use of naphthalimide-based probes for the detection of mercury in a variety of environments, whether it being in living cells [8], zebrafish model organisms [9], or even in a variety of polar and organic solvents [10]. Additionally, the diverse photophysical characteristics of the naphthalimide structure can be effectively modified by appropriate structural alterations, like functionalizing the aromatic naphthalene moiety and the 'N-imide site' [11].…”
Section: Introductionmentioning
confidence: 99%